A Mg-MgH2 composite hydrogen storage material containing MXene catalyst and its preparation method

CN118619204BActive Publication Date: 2026-11-03CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410757842.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2026-11-03
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

Existing Mg-based hydrogen storage materials are expensive to prepare, energy-intensive, and have poor hydrogen absorption and desorption performance. In particular, the preparation process of MgH2 is demanding, which leads to the high cost of hydrogen storage materials.

Method used

Mg-MgH2 composite hydrogen storage material was prepared by directly mixing MXene catalyst with Mg powder and then performing hydrogenation ball milling. The multivalent transition metal elements and layered structure of MXene catalyst were used to improve the diffusion and adsorption of hydrogen molecules, thereby achieving efficient conversion of Mg phase to MgH2 phase.

Benefits of technology

It reduces the raw material cost of MgH2 preparation, improves the hydrogen absorption and desorption performance of hydrogen storage materials, with an initial hydrogen desorption temperature ≤200℃, and a hydrogen desorption amount ≥5.0wt.% within 30 minutes at 300℃, making it suitable for various hydrogen storage environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619204B_ABST
    Figure CN118619204B_ABST
Patent Text Reader

Abstract

The application relates to an Mg-MgH2 composite hydrogen storage material containing a MXene catalyst and a preparation method thereof, and belongs to the technical field of solid-state hydrogen storage materials. At least one of the problems in the prior art, such as high preparation cost, high energy consumption of raw material MgH2 of an Mg-based hydrogen storage material, poor hydrogen absorption and release performance of an existing solid-state hydrogen storage material and the like, is solved. The application provides a preparation method of an Mg-MgH2 composite hydrogen storage material containing a MXene catalyst, wherein the method directly mixes a MXene catalyst and Mg powder, and then hydrogen ball-mills to prepare the Mg-MgH2 composite hydrogen storage material; wherein the MXene catalyst is prepared from an MAX phase, and the MAX phase is one of Ti3AlC2, Ti2AlC, Nb3AlC2 and V2AlC. The application directly uses Mg powder as a raw material to prepare the Mg-MgH2 composite hydrogen storage material, so that the preparation cost and energy consumption are greatly reduced; and the catalytic performance and structural characteristics of the MXene catalyst are fully utilized, so that the conversion from an Mg phase to an MgH2 phase is realized, and the hydrogen absorption and release performance of the composite hydrogen storage material is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state hydrogen storage materials technology, and in particular to a Mg-MgH2 composite hydrogen storage material containing an MXene catalyst and its preparation method. Background Technology

[0002] The efficient and safe storage and transportation of hydrogen is a bottleneck restricting the large-scale application of hydrogen energy. Among these technologies, solid-state hydrogen storage technology has advantages over high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage, such as high volumetric hydrogen storage density and good safety. Among solid-state hydrogen storage materials, Mg has a high mass hydrogen storage density (7.6 wt.%), reversible hydrogen absorption and desorption processes, and is abundant. However, the hydrogen absorption and desorption kinetics of this type of material are poor, and the absorption and desorption temperatures are too high, limiting its practical application.

[0003] Existing technologies for utilizing the hydrogen storage performance of catalytically modified Mg first require long-term hydrogenation of pure Mg under high temperature and high pressure conditions (temperature above 400℃, hydrogen pressure greater than 3MPa) or synthesis of MgH2 through hydrogenation combustion. Only after adding a catalyst to MgH2 can a Mg-based composite hydrogen storage material with superior hydrogen storage performance be obtained.

[0004] Two-dimensional transition metal carbides (MXenes) exhibit significant effects in catalyzing hydrogen absorption and desorption reactions in solid-state hydrogen storage materials due to their unique layered structure and the presence of multivalent transition metal elements. However, when using this catalyst to catalytically modify Mg-based solid-state hydrogen storage materials, it is often necessary to pre-hydrogenate Mg to form MgH2. For example, in patent application number 202310698813.1, a composite hydrogen storage material was prepared using a sulfur-nitrogen-doped MXene hydrogen storage catalyst and high-purity MgH2, which could release 5.31 wt.% hydrogen within 5 minutes.

[0005] In summary, high-purity MgH2 is currently used as a raw material to prepare Mg-based hydrogen storage materials, thereby obtaining good hydrogen storage performance (mainly referring to hydrogen storage capacity and hydrogen absorption and desorption performance). However, the preparation cost of MgH2 is high, energy consumption is large, and the process conditions are harsh, which makes the preparation cost of hydrogen storage materials remain high. Summary of the Invention

[0006] Based on the above analysis, the present invention aims to provide a Mg-MgH2 composite hydrogen storage material containing an MXene catalyst and its preparation method, in order to solve at least one of the problems of high cost of MgH2 raw material preparation, high energy consumption, and poor hydrogen absorption and desorption performance of existing solid hydrogen storage materials.

[0007] This invention discloses a method for preparing Mg-MgH2 composite hydrogen storage material containing MXene catalyst. The method involves directly mixing MXene catalyst with Mg powder and then ball milling with hydrogen to obtain Mg-MgH2 composite hydrogen storage material.

[0008] The MXene catalyst is prepared from a MAX phase, which is one of Ti3AlC2, Ti2AlC, Nb3AlC2, and V2AlC.

[0009] The preparation method includes the following specific steps:

[0010] S1: Weigh a certain amount of LiF powder and dissolve it in concentrated hydrochloric acid to obtain an etching solution for etching the MAX phase;

[0011] S2: Weigh out the MAX phase powder and add it to the etching solution in small amounts several times. After all the MAX phase powder has been added, heat the solution to carry out the etching reaction.

[0012] S3: After etching, the solution is centrifuged, washed, and filtered until the supernatant is neutral. The filtered product is then freeze-dried to obtain a layered MXene catalyst with the Al atomic layer etched away.

[0013] S4: After mixing the MXene catalyst with high-purity Mg powder in a glove box, the mixture is added to a ball mill jar and filled with hydrogen gas for ball milling to finally obtain a Mg / MgH2 composite hydrogen storage material containing the MXene catalyst.

[0014] Specifically, the concentration of concentrated hydrochloric acid in step S1 is 9–12 mol / L, and the mass concentration of LiF in the etching solution is 0.06–0.08 g / mL.

[0015] Specifically, the ratio of MAX phase powder to etching solution in step S2 is 1g:10-20mL.

[0016] Specifically, the operation of adding MAX phase powder in step S2 is as follows: each time, a small amount of MAX phase powder is added to the etching solution. After the generated bubbles completely disappear, another small amount is added. This process is repeated multiple times until all the MAX phase powder is added.

[0017] Specifically, the etching parameters in step S2 are: heating temperature of 40℃~60℃ and reaction time of 48~72h.

[0018] Specifically, in step S4, the mass of the MXene catalyst accounts for 3 to 10% of the total mass of the MXene catalyst and Mg powder;

[0019] The hydrogen pressure in the grinding jar is 1-3 MPa, the ball-to-material ratio is 20-40:1, the ball milling speed is 300-500 rpm, and the ball milling time is 5-20 h.

[0020] The present invention also discloses a Mg-MgH2 composite hydrogen storage material containing an MXene catalyst, wherein the composite hydrogen storage material is prepared by the above preparation method.

[0021] Furthermore, the form in which Mg exists in the composite hydrogen storage material satisfies the following conditions:

[0022] The sum of the relative Mg content of the Mg phase with space group P63 / mmc and the MgH2 phase with space group P42 / mnm is ≥95%, and 50% ≤ the relative Mg content of the MgH2 phase with space group P42 / mnm is ≤95%, and the sum of the relative Mg content of MgO and other impurity phases is ≤5%.

[0023] Wherein, the relative Mg content = the mass of Mg in the corresponding phase / the total mass of Mg.

[0024] Specifically, the initial hydrogen release temperature of the composite hydrogen storage material is ≤200℃, and the hydrogen release amount within 30 minutes at 300℃ is ≥5.0 wt.%.

[0025] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0026] 1. This invention utilizes the characteristics of MXene catalyst to achieve efficient conversion of Mg phase to MgH2 phase during hydrogenation ball milling, eliminating the need for high-purity MgH2 as raw material, thus significantly reducing process requirements and costs.

[0027] This invention selects one of Ti3AlC2, Ti2AlC, Nb3AlC2, and V2AlC as the MAX catalyst to obtain the corresponding MXene catalyst. The synthesis process of the MXene catalyst is relatively mature, the raw materials are readily available, the preparation process is controllable, and it has the characteristics of high specific surface area, excellent conductivity, and strong thermal stability. During the hydrogenation ball milling process, the transition metal elements in the MXene, such as Ti (+4, +3, and +2), Nb (+5, +4, +3, and +2), and V (+6, +5, +4, +3, and +2), all have multiple valence states, providing a variety of active sites. Furthermore, due to its unique layered structure and high specific surface area, the number and distribution of transition metal active sites are further increased, which is conducive to the diffusion and adsorption of hydrogen molecules. This results in more complete contact between high-pressure hydrogen and Mg powder during ball milling, leading to a more thorough reaction and achieving efficient conversion of the Mg phase to the MgH2 phase during hydrogenation ball milling. When the mass of MXene catalyst added during the preparation process accounts for 3 to 10% of the total mass of MXene catalyst and Mg powder, up to 85.84 wt.% of Mg can be converted into the MgH2 phase, which significantly reduces the cost of raw materials. Moreover, the process conditions are mild and the operation is easy.

[0028] 2. This invention innovatively reveals that the content of MgH2 in Mg-based hydrogen storage materials containing MXene catalysts is not completely positively correlated with hydrogen storage performance, or that when the proportion of MgH2 phase reaches a certain value, the hydrogen storage performance increases extremely slowly.

[0029] As can be seen from Examples 1-6 and Comparative Examples 1-3, especially Examples 2-4 and Comparative Example 2 (the comparative example is a counterexample), when the relative content of Mg in the MgH2 phase is greater than 50%, further increasing the proportion of the MgH2 phase does not significantly improve the hydrogen storage performance of the hydrogen storage material; therefore, it is not necessary to pursue the complete conversion of the Mg phase into the MgH2 phase during the preparation process.

[0030] Meanwhile, the objective laws revealed by this invention can also provide reference and inspiration for the preparation and optimization of other Mg-based hydrogen storage materials in this field. That is to say, those skilled in the art do not need to pursue the use of only high-purity MgH2 powder as raw material in the preparation of other Mg-based hydrogen storage materials. Instead, they can try to mix Mg powder and MgH2 powder to obtain hydrogen storage materials with excellent hydrogen storage performance and significantly reduce the preparation cost. It is worth emphasizing that whether the above laws apply or need to be adjusted for Mg-based hydrogen storage materials that do not contain MXene catalysts still needs further research and confirmation.

[0031] 3. The composite hydrogen storage material prepared by this invention exhibits excellent hydrogen storage performance and good hydrogen absorption and desorption properties. During the preparation process, most of the Mg phase is converted to the MgH2 phase, ensuring the basic hydrogen storage performance of the composite material. Furthermore, due to the high specific surface area, excellent conductivity, good chemical stability, and strong thermal stability of the MXene catalyst, the contact area between hydrogen and Mg / MgH2 is increased, accelerating electron transfer and thus improving the hydrogen absorption and desorption reaction rate. Therefore, the composite hydrogen storage material provided by this invention has excellent hydrogen absorption and desorption performance, with an initial hydrogen desorption temperature ≤200℃ and a hydrogen desorption rate ≥5.0 wt.% within 30 minutes at 300℃. Therefore, the above-mentioned composite hydrogen storage material can adapt well to various hydrogen storage environments and meet different hydrogen storage requirements.

[0032] 4. The catalyst preparation method provided by this invention is simple and the raw materials are readily available, making it suitable for large-scale production.

[0033] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0034] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0035] Figure 1 The TPD curves are for Examples 1-6 and Comparative Examples 1-3;

[0036] Figure 2 Hydrogen desorption curves (300°C) for Examples 1-3, 6 and Comparative Examples 1-3;

[0037] Figure 3 The image shows the XRD pattern and Rietveld refinement result of Example 1. Detailed Implementation

[0038] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0039] This invention discloses a method for preparing Mg-MgH2 composite hydrogen storage material containing MXene catalyst. The method involves directly mixing MXene catalyst with Mg powder and then ball milling with hydrogen to obtain Mg-MgH2 composite hydrogen storage material.

[0040] The MXene catalyst is prepared from a MAX phase, which is one of Ti3AlC2, Ti2AlC, Nb3AlC2, and V2AlC.

[0041] The Ti3C2, Ti2C, Nb3C2, and V2C phases obtained from the above-mentioned MAX phases possess characteristics such as high specific surface area, excellent electrical conductivity, good chemical stability, and strong thermal stability. Therefore, they can increase the contact area with hydrogen storage materials, accelerate the hydrogen absorption and desorption reaction rate, and adapt well to various hydrogen storage environments, meeting different hydrogen storage requirements. Furthermore, the synthesis process of the MXene is relatively mature, the raw materials are readily available, and the preparation process is controllable. During the hydrogenation ball milling process, the transition metal elements in the MXene, such as Ti (+4, +3, and +2), Nb (+5, +4, +3, and +2), and V (+6, +5, +4, +3, and +2), all possess multiple valence states. These transition metals interact with hydrogen molecules through their different oxidation states, providing multiple active sites that can catalyze the dissociation and recombination of hydrogen molecules. In addition, the multi-valence characteristics of the transition metals allow them to flexibly undergo redox reactions during the reaction process, thereby effectively reducing the energy barrier for hydrogen absorption and release. Meanwhile, MXene, through its layered structure and high specific surface area, further increases the number and distribution of transition metal active sites, making the diffusion and adsorption of hydrogen molecules more efficient, and also helps the transformation of Mg phase to MgH2 during hydrogenation ball milling.

[0042] The preparation method includes the following specific steps:

[0043] S1: Weigh a certain amount of LiF powder and dissolve it in concentrated hydrochloric acid to obtain an etching solution for etching the MAX phase;

[0044] S2: Weigh out the MAX phase powder and add it to the etching solution in small amounts several times. After all the MAX phase powder has been added, heat the solution to carry out the etching reaction.

[0045] S3: After etching, the solution is centrifuged, washed, and filtered until the supernatant is neutral. The filtered product is then freeze-dried to obtain a layered MXene catalyst with the Al atomic layer etched away.

[0046] S4: After mixing the MXene catalyst with high-purity Mg powder in a glove box, the mixture is added to a ball mill jar and filled with hydrogen gas for ball milling to finally obtain a Mg / MgH2 composite hydrogen storage material containing the MXene catalyst.

[0047] Specifically, in step S1, the concentration of concentrated hydrochloric acid is 9–12 mol / L, and the mass concentration of LiF in the etching solution is 0.06–0.08 g / mL. When the LiF concentration is below 0.06 g / mL, sufficient F cannot be provided. - With H in concentrated hydrochloric acid + The etching of Al atoms is accomplished by the formation of HF, while when the LiF concentration is higher than 0.08 g / mL, F... - It exists as a terminating group on the surface of MXene, affecting the catalytic activity of MXene.

[0048] Specifically, in step S2, the ratio of MAX phase powder to etching solution is 1g:10-20mL. When the ratio of MAX phase powder to etching solution is less than 1g:20ml, the Al atoms in the MAX phase cannot be completely etched, affecting the formation of the layered structure. When the ratio of MAX phase powder to etching solution is greater than 1g:10ml, the excessively high etching solution concentration will affect the surface chemical properties of MXene, thereby weakening its catalytic activity.

[0049] Specifically, the operation of adding MAX phase powder in step S2 is as follows: A small amount of MAX phase powder is added to the etching solution each time. Once the generated bubbles have completely disappeared, another small amount is added, and this process is repeated several times until all the MAX phase powder has been added. This operation is to avoid adding too much MAX phase powder at once, which could cause the etching solution to overflow or splash due to the instantaneous generation of a large number of bubbles, thus preventing potential hazards.

[0050] Specifically, the etching parameters in step S2 are: heating temperature of 40℃~60℃ and reaction time of 48~72h. If the heating temperature is too high, the etching reaction is violent, the etching solution splashes, the preparation process is dangerous, and the layered structure of MXene is altered. If the heating temperature is too low, the provided reaction energy is insufficient to complete the etching.

[0051] Specifically, in step S3, the centrifugation washing rate is 4000–11000 rpm, for example, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000 rpm, repeated 3–5 times, with each centrifugation lasting 3–10 minutes, for example, 3, 4, 5, 6, 7, 8, 9, 10 minutes. After multiple centrifugation washings at different rates and for different times, the etching solution in MXene can be removed, and the yield can be improved.

[0052] Specifically, in step S4, the mass of MXene catalyst accounts for 3 to 10% of the total mass of MXene catalyst and Mg powder. If the amount of MXene catalyst added is too low, the Mg phase will not be fully converted into the MgH2 phase (more than 50%), resulting in poor hydrogen storage performance. If the amount of MXene catalyst added is too high, too much MXene catalyst will remain in the final product, resulting in a reduction in hydrogen storage capacity.

[0053] It is worth emphasizing that a portion of the added MXene catalyst participates in the reaction of Mg phase to MgH2 phase and is consumed. The remaining MXene catalyst improves the hydrogen absorption and desorption performance of the composite hydrogen storage material. However, the MXene catalyst itself does not have hydrogen storage capacity. Therefore, too much residual MXene catalyst will also affect the hydrogen storage capacity (but will not affect the hydrogen absorption and desorption rate).

[0054] The hydrogen pressure in the grinding jar is 1–3 MPa, for example, 1, 1.5, 2, 2.5, 3 MPa; the ball-to-material ratio is 20–40:1, for example, 20:1, 25:1, 30:1, 35:1, 40:1; the ball milling speed is 300–500 rpm, for example, 300, 350, 400, 450, 500 rpm; the ball milling time is 5–20 h, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 h.

[0055] When the hydrogen pressure is too low, the Mg phase cannot be fully converted into the MgH2 phase (above 50%), thus affecting the hydrogen storage performance. When the hydrogen pressure is too high, the conversion rate of the MgH2 phase will not continue to increase, and excessively high hydrogen pressure is dangerous. Regarding the ball-to-powder ratio, a low ball-to-powder ratio will reduce the collision frequency and energy between MXene and high-purity Mg powder, resulting in low conversion efficiency of the Mg phase to the MgH2 phase. A high ball-to-powder ratio will lead to an increase in temperature during the grinding process, affecting the chemical stability of MXene and high-purity Mg powder. Regarding the ball milling time, a longer ball milling time usually results in finer particles, which is not conducive to the use of hydrogen storage materials. A shorter time results in incomplete conversion of the Mg phase to the MgH2 phase, causing a decrease in hydrogen storage performance. Regarding the ball milling rate, a low ball milling rate results in small relative motion between MXene and high-purity Mg powder, which cannot provide enough energy for the conversion of Mg to MgH2. An excessively high ball milling rate leads to uneven particle breakage and may even cause agglomeration, resulting in a decrease in hydrogen storage capacity.

[0056] The present invention also discloses a Mg-MgH2 composite hydrogen storage material containing an MXene catalyst, wherein the composite hydrogen storage material is prepared by the above preparation method.

[0057] Furthermore, the form in which Mg exists in the composite hydrogen storage material satisfies the following conditions:

[0058] The sum of the relative Mg content of the Mg phase with space group P63 / mmc and the MgH2 phase with space group P42 / mnm is ≥95%, and 50% ≤ the relative Mg content of the MgH2 phase with space group P42 / mnm is ≤95%, and the sum of the relative Mg content of MgO and other impurity phases is ≤5%.

[0059] Wherein, the relative Mg content = the mass of Mg in the corresponding phase / the total mass of Mg.

[0060] According to experimental data (refer to Examples 2-4 and Comparative Example 2), when the relative Mg content of the MgH2 phase is <50%, the hydrogen storage capacity will decrease significantly; when the relative Mg content of the MgH2 phase is ≥50%, especially ≥60%, the hydrogen storage capacity (mainly referring to hydrogen storage capacity) does not change significantly, but a higher relative Mg content of the MgH2 phase helps to reduce the initial hydrogen release temperature.

[0061] It is worth emphasizing that the final composite hydrogen storage material product contains a certain amount of MXene catalyst, but since it is dispersed in the various phases of Mg in the form of two-dimensional layered particles, it is difficult to detect accurately. Therefore, this invention limits the amount added during the preparation process.

[0062] Specifically, the initial hydrogen release temperature of the composite hydrogen storage material is ≤200℃, and the hydrogen release amount within 30 minutes at 300℃ is ≥5.0 wt.%.

[0063] Example 1

[0064] 3.2 g of LiF was dissolved in 40 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Ti3AlC2 MAX phase was weighed and added to the etching solution in small batches. Each batch was added only after the bubbles generated during etching had completely disappeared. This process was repeated until all Ti3AlC2 was added. The water bath temperature was adjusted to 45 °C, and the reaction was carried out for 48 h to complete the etching process. The etched product was washed by centrifugation using 1 mol / L hydrochloric acid and distilled water. The first three centrifugations were performed at 5000 rpm, and subsequent centrifugations were increased to 10000 rpm. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Ti3C2 MXene catalyst.

[0065] The obtained Ti3C2 MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 3:97 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 400 rpm, to obtain a Mg / MgH2 composite hydrogen storage material containing the Ti3C2MXene catalyst.

[0066] The hydrogen storage performance of the material was determined using a Sievert's apparatus. Test method: Approximately 1g of sample was taken and evacuated to <0.0001MPa at 300℃. Then, at 300℃ and a hydrogen pressure of 3MPa, the sample was saturated with hydrogen absorption. After cooling to room temperature in the furnace, the temperature was increased at a rate of 1℃ / min, and the hydrogen release rate (TPD) curve was measured. For the hydrogen release capacity test, after saturation at a hydrogen pressure of 3MPa, the hydrogen release was tested at 300℃ against an ambient hydrogen pressure of less than 0.01MPa.

[0067] Depend on Figure 1 It can be seen that the initial hydrogen release temperature in Example 1 is 183°C. Figure 2 As can be seen, at 300°C, the hydrogen release rate in Example 1 was 5.1 wt.% within 30 minutes.

[0068] Example 2

[0069] 2.4 g of LiF was dissolved in 40 ml of 9 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Ti3AlC2 MAX phase was weighed and added to the etching solution in small batches. Each batch was added only after the bubbles generated during etching had completely disappeared. This process was repeated until all Ti3AlC2 was added. The water bath temperature was adjusted to 60℃, and the reaction was carried out for 72 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The first three centrifugations were performed at 5000 rpm, and subsequent centrifugations were increased to 10000 rpm. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Ti3C2 MXene catalyst.

[0070] The obtained Ti3C2 MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 5:95 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 15 h, and the ball milling rate was 400 rpm, thus obtaining a Mg / MgH2 composite hydrogen storage material containing the Ti3C2 MXene catalyst.

[0071] The relative contents of the Mg phase and MgH2 phase in Example 2 were tested according to the method in Example 1, which were 20.77 wt.% and 75.96 wt.%, respectively. The initial hydrogen release temperature was 163 °C, and the hydrogen release amount at 300 °C for 30 min was 5.3 wt.%.

[0072] Example 3

[0073] 3.2 g of LiF was dissolved in 40 ml of 9 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Ti3AlC2 MAX phase was weighed and added to the etching solution in small batches. Each batch was added only after the bubbles generated during etching had completely disappeared. This process was repeated until all Ti3AlC2 was added. The water bath temperature was adjusted to 60℃, and the reaction was carried out for 48 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The first three centrifugations were performed at 5000 rpm, and subsequent centrifugations were increased to 10000 rpm. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Ti3C2 MXene catalyst.

[0074] The obtained Ti3C2 MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 10:90 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated, and then filled with hydrogen gas at approximately 2 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 450 rpm, thus obtaining a Mg / MgH2 composite hydrogen storage material containing the Ti3C2MXene catalyst.

[0075] The relative contents of the Mg phase and MgH2 phase in Example 3 were tested according to the method in Example 1, which were 10.29 wt.% and 85.84 wt.%, respectively. The initial hydrogen release temperature was 152°C, and the hydrogen release amount after 30 minutes at 300°C was 5.4 wt.%.

[0076] Example 4

[0077] 2.8 g of LiF was dissolved in 40 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Ti₂AlC MAX phase was weighed and added to the etching solution in small amounts each time. Each time, a small amount was added after the bubbles generated during etching completely disappeared. This process was repeated several times until all Ti₂AlC was added. The water bath temperature was adjusted to 60 °C, and the reaction was carried out for 72 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The centrifugation rate was 5000 rpm for the first three times, and then increased to 10000 rpm for subsequent centrifugation. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Ti₂C MXene catalyst.

[0078] The obtained Ti2C MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 5:95 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 30:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 2 MPa for ball milling. The ball milling time was 20 h, and the ball milling rate was 300 rpm, to obtain a Mg / MgH2 composite hydrogen storage material containing the Ti2C MXene catalyst.

[0079] The relative contents of the Mg phase and MgH2 phase in Example 4 were tested according to the method in Example 1, and were 10.29 wt.% and 85.84 wt.%, respectively. The initial hydrogen release temperature was 195 °C; the hydrogen release amount at 300 °C for 30 min was 5.2 wt.%.

[0080] Example 5

[0081] 2.6 g of LiF was dissolved in 40 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Nb4AlC3 MAX phase was weighed and added to the etching solution in small batches. Each batch was added only after the bubbles generated during etching had completely disappeared. This process was repeated until all Nb4AlC3 was added. The water bath temperature was adjusted to 60 °C, and the reaction was carried out for 48 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The first three centrifugations were performed at 5000 rpm, and subsequent centrifugations were increased to 10000 rpm. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Nb4C3 MXene catalyst.

[0082] The obtained Nb4C3 MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 7:93 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 20:1. The ball mill jar was repeatedly evacuated, and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 400 rpm, to obtain a Mg / MgH2 composite hydrogen storage material containing the Nb4C3 MXene catalyst.

[0083] The relative contents of the Mg phase and MgH2 phase in Example 5 were tested according to the method in Example 1, and were 15.26 wt.% and 80.66 wt.%, respectively. The initial hydrogen release temperature was 176 °C; the hydrogen release amount at 300 °C for 30 min was 5.1 wt.%.

[0084] Example 6

[0085] 1.6 g of LiF was dissolved in 20 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 1 g of V₂AlC MAX phase was weighed and added to the etching solution in small amounts each time. Each time, a small amount was added after the bubbles generated during etching completely disappeared. This process was repeated several times until all V₂AlC was added. The water bath temperature was adjusted to 60 °C, and the reaction was carried out for 48 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The centrifugation rate was 5000 rpm for the first three times, and then increased to 10000 rpm for subsequent centrifugation. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the V₂C MXene catalyst.

[0086] The obtained V2C MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 10:90 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 400 rpm, to obtain a Mg / MgH2 composite hydrogen storage material containing the V2C MXene catalyst.

[0087] The relative contents of the Mg phase and MgH2 phase in Example 5 were tested according to the method in Example 1, and were 11.70 wt.% and 83.90 wt.%, respectively. The initial hydrogen release temperature was 182 °C; the hydrogen release amount at 300 °C for 30 min was 5.3 wt.%.

[0088] Comparative Example 1

[0089] In the glove box, weigh out the same amount of Mg powder as in Example 1, add it to the ball mill jar, and add stainless steel balls with a ball-to-material mass ratio of 40:1. After repeatedly evacuating the ball mill jar, fill it with hydrogen gas at about 3 MPa for ball milling. The ball milling time is 10 hours and the ball milling speed is 400 rpm.

[0090] The hydrogen storage material samples obtained in Example 1 and Comparative Example 1 were subjected to powder X-ray diffraction (PXRD) tests using a Cu target, 40 kV, 40 mA, and 2° / min, with 2θ ranging from 5° to 90°. The obtained XRD data were then subjected to Rietveld full-spectrum fitting using Fullprof to obtain the phase composition of the alloy. Figure 3 The figure shows the Rietveld full spectrum fitting diagram of Example 1. As can be seen from the figure, due to the small mass fraction of Ti3C2 MXene and the poor crystallinity of Ti3C2, no diffraction peak of this substance appeared in XRD in Example 1. Both Example 1 and Comparative Example 1 consist of a Mg phase with space group P63 / mmc, a MgH2 phase with space group P42 / mnm, and a small amount of MgO phase with space group Fm-3m. Table 1 lists the phase composition of Example 1 and Comparative Example 1. The relative contents of the Mg phase and MgH2 phase in Example 1 are 36.90 wt.% and 62.07 wt.%, respectively, while the relative contents of the Mg phase and MgH2 phase in Comparative Example 1 are 67.98 wt.% and 28.79 wt.%, respectively. The addition of 3 wt.% Ti3C2 MXene significantly promoted the transformation of Mg to MgH2.

[0091] The hydrogen storage performance of the material was determined using a Sievert's apparatus. Test method: Approximately 1g of sample was taken and evacuated to <0.0001MPa at 300℃. Then, at 300℃ and a hydrogen pressure of 3MPa, the sample was saturated with hydrogen absorption. After cooling to room temperature in the furnace, the temperature was increased at a rate of 1℃ / min, and the hydrogen release rate (TPD) curve was measured. For the hydrogen release capacity test, after saturation at a hydrogen pressure of 3MPa, the hydrogen release was tested at 300℃ against an ambient hydrogen pressure of less than 0.01MPa.

[0092] Depend on Figure 1 As can be seen, the initial hydrogen release temperature of Example 1 was 183°C, while that of Comparative Example 1 was 317°C. The initial hydrogen release temperature of the Mg / MgH2 composite hydrogen storage material formed after adding 3 wt.% Ti3C2 MXene was significantly reduced. Figure 2 As can be seen, at 300°C for 30 minutes, the hydrogen release of Example 1 was 5.1 wt.%, while the hydrogen release of Comparative Example 1 was only about 0.1 wt.%.

[0093] Comparative Example 2

[0094] 3.2 g of LiF was dissolved in 40 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 2 g of Ti3AlC2 MAX phase was weighed and added to the etching solution in small batches. Each batch was added only after the bubbles generated during etching had completely disappeared. This process was repeated until all Ti3AlC2 was added. The water bath temperature was adjusted to 45 °C, and the reaction was carried out for 48 h to complete the etching process. The etched product was washed by centrifugation using 1 mol / L hydrochloric acid and distilled water. The first three centrifugations were performed at 5000 rpm, and subsequent centrifugations were increased to 10000 rpm. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the Ti3C2 MXene catalyst.

[0095] The obtained Ti3C2 MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 1:99 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 400 rpm, thus obtaining a Mg / MgH2 composite hydrogen storage material containing the Ti3C2MXene catalyst.

[0096] The relative contents of the Mg phase and MgH2 phase in Comparative Example 2 were tested according to the method in Example 1, and were 55.43 wt.% and 43.02 wt.%, respectively. The initial hydrogen release temperature was 209°C; the hydrogen release amount at 300°C for 30 minutes was 3.8 wt.%.

[0097] Comparative Example 3

[0098] 1.6 g of LiF was dissolved in 20 ml of 12 mol / L concentrated hydrochloric acid. After thorough mixing, an etching solution was obtained. 1 g of V₂AlC MAX phase was weighed and added to the etching solution in small amounts each time. Each time, a small amount was added after the bubbles generated during etching completely disappeared. This process was repeated several times until all V₂AlC was added. The water bath temperature was adjusted to 60 °C, and the reaction was carried out for 48 h to complete the etching. The etched product was washed by centrifugation with 1 mol / L hydrochloric acid and distilled water. The centrifugation rate was 5000 rpm for the first three times, and then increased to 10000 rpm for subsequent centrifugation. Washing was completed when the supernatant became neutral. The product was then freeze-dried to obtain the V₂C MXene catalyst.

[0099] The obtained V2C MXene catalyst was premixed with high-purity Mg powder with a purity of not less than 99.5 wt.% at a mass ratio of 15:85 in a glove box. After uniform mixing, the mixture was added to a ball mill jar, along with stainless steel balls at a ball-to-material mass ratio of 40:1. The ball mill jar was repeatedly evacuated and then filled with hydrogen gas at approximately 3 MPa for ball milling. The ball milling time was 10 h, and the ball milling rate was 400 rpm, thus obtaining a Mg / MgH2 composite hydrogen storage material containing the V2C MXene catalyst.

[0100] The relative contents of the Mg phase and MgH2 phase in Comparative Example 3 were tested according to the method in Example 1, which were 2.86 wt.% and 96.02 wt.%, respectively. The initial hydrogen release temperature was 173 °C, and the hydrogen release amount at 300 °C for 30 min was 4.9 wt.%.

[0101] Table 1 Hydrogen storage performance of Examples 1-6 and Comparative Examples 1-3

[0102]

[0103]

[0104] From Table 1 and Figure 1 , 2 As can be seen from the comparison of Examples 1, 2, and 3 with Comparative Examples 1 and 2, when no MXene catalyst was added in Comparative Example 1, the hydrogen storage material after hydrogenation ball milling contained only 28.79 wt.% MgH2, and the initial hydrogen release temperature was about 317°C.

[0105] When 1 wt.% Ti3C2 MXene was added to Comparative Example 2, the relative content of the MgH2 phase increased slightly to 43.02 wt.%. However, the synergistic catalytic performance of the MgH2 phase with the Mg phase remained poor, even with a lower content. The initial hydrogen release temperature of Comparative Example 2 was above 200°C, at 209°C, and the hydrogen release amount within 30 minutes at 300°C was only 3.8 wt.%. Therefore, when the Ti3C2 MXene content of the catalyst is low, the transformation of Mg to MgH2 is limited. Furthermore, due to the low MgH2 phase content in the prepared composite material, the catalytic modification is not significant, the initial hydrogen release temperature remains high, and the kinetic performance is poor.

[0106] After increasing the amount of MXene catalyst added, compared with Comparative Example 6 and Comparative Example 3, when 15 wt.% of V2CMXene was added, the relative content of the MgH2 phase was further increased to 96.02 wt.%, and the initial hydrogen release temperature was further reduced from 182°C in Example 6 to 173°C. However, since the catalyst could not provide hydrogen storage capacity, the overall hydrogen storage capacity of the composite material decreased, and the hydrogen release capacity at 300°C for 30 min decreased to 4.9 wt.%.

[0107] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a Mg-MgH2 composite hydrogen storage material containing an MXene catalyst, characterized in that, The specific steps include the following: S1: Weigh a certain amount of LiF powder and dissolve it in concentrated hydrochloric acid to obtain an etching solution for etching the MAX phase. The mass concentration of LiF in the etching solution is 0.06-0.08 g / mL. S2: Weigh out the MAX phase powder and add it to the etching solution in small amounts several times. After all the MAX phase powder has been added, heat the solution to carry out the etching reaction. The etching reaction temperature is 40~60℃ and the time is 48~72 h. The MAX phase is one of Ti3AlC2, Ti2AlC, Nb3AlC2, and V2AlC. S3: After etching, the solution is centrifuged, washed, and filtered until the supernatant is neutral. The filtered product is then freeze-dried to obtain a layered MXene catalyst with the Al atomic layer etched away. S4: Mix the MXene catalyst with high-purity Mg powder in a glove box, add it to a ball mill jar, and fill it with hydrogen gas for ball milling to finally obtain a Mg / MgH2 composite hydrogen storage material containing MXene catalyst; the mass of MXene catalyst accounts for 3 to 10% of the total mass of MXene catalyst and Mg powder; the hydrogen pressure in the ball mill jar is 1 to 3 MPa.

2. The preparation method according to claim 1, characterized in that: The concentration of concentrated hydrochloric acid mentioned in step S1 is 9–12 mol / L.

3. The preparation method according to claim 1, characterized in that: The ratio of MAX phase powder to etching solution in step S2 is 1 g: 10-20 mL.

4. The preparation method according to claim 1, characterized in that: The specific operation of adding MAX phase powder in step S2 is as follows: each time, a small amount of MAX phase powder is added to the etching solution. After the generated bubbles completely disappear, a small amount is added again. This process is repeated multiple times until all the MAX phase powder is added.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass of MXene catalyst accounts for 7-10% of the total mass of MXene catalyst and Mg powder; the hydrogen pressure in the mill is 2.5-3 MPa, the ball-to-material ratio is 20-40:1, the ball milling rate is 300-500 rpm, and the ball milling time is 5-20 h.

6. A Mg-MgH2 composite hydrogen storage material containing an MXene catalyst, characterized in that, The composite hydrogen storage material is prepared by the preparation method described in any one of claims 1 to 5.

7. The Mg-MgH2 composite hydrogen storage material according to claim 6, characterized in that, The form in which Mg exists in the composite hydrogen storage material satisfies the following conditions: The sum of the relative Mg contents of the Mg phase with space group P63 / mmc and the MgH2 phase with space group P42 / mnm is ≥95%, and 50% ≤ the relative Mg contents of the MgH2 phase with space group P42 / mnm is ≤95%, and the sum of the relative Mg contents of MgO and other impurity phases is ≤5%. Wherein, the relative Mg content = the mass of Mg in the corresponding phase / the total mass of Mg.

Citation Information

Patent Citations

  • Sulfur-nitrogen doped MXene hydrogen storage material catalyst, hydrogen storage material containing the catalyst and preparation method

    CN116726970B

  • Composite hydrogen storage material with improved hydrogen absorption and desorption performance and preparation method thereof

    CN116143070A

  • MXene hydrogen storage material catalyst, hydrogen storage material containing catalyst and preparation method

    CN117085713A